SOETOMO SCORE AS A PREDICTOR OF HIV-ASSOCIATED NEUROCOGNITIVE DISORDERS - Rudy Qimindra, Fajar; Hamdan, Muhammad; Wisnujono, Riani; Haryono, Yudha; Machin, Abdulloh (International Journal of Psychosocial Rehabilitation, 2020)
Background HIV-Associated Neurocognitive Disorders (HAND) was one of the neurological complications of HIV infection. However, no biomarkers have been sufficiently validated for prognosis. Objective: To develop a scoring system and determine prognostic values of the Soetomo Score as a Predictor of HIV-Associated Neurocognitive Disorders (SSP HAND). Methods: The case-control study was performed at the UPIPI outpatient clinic. The examination is performed using MoCa-Ina.Eight parameters that were possible predictors of HAND were analyzed by bivariate and multivariate. Results were analyzed using a calibration test and a discrimination test to produce an Area Under Curve (AUC) value. The cut-off point could make identification of good and bad prognostics. Results: The equation of SSP HAND was Y=-4.164+1.249 score total of SSP HAND. The AUC value of this score was 80.9% (95% CI=71.1%-90.6%). The value of SSP HAND was ≥3.5, which means that the sensitivity was 74.4% and the specificity was 79.5%. Subjects with scores 0–3 had good prognostic, while those with scores 4–5 had bad prognostic. Conclusion: The value of SSP HAND ≥3.5 could make a good prediction of HAND.